The quest for morally competent future Muslim accountants - Zubairu, Umaru; Ismail, Suhaiza; Fatima, Abdul Hamid (Emerald Group Publishing Ltd., 2019)
Purpose: The moral credibility of accountants has been battered for over two decades because of a seemingly unending series of accounting scandals. The inclusion of ethics education in the accounting curricula has been advocated as one option through which a new generation of morally competent accountants can be produced. The purpose of this paper is to present the results of a study that sought to determine the success of this strategy by measuring the moral competencies of 160 final-year Muslim accounting students enrolled in two Islamic-university accounting programs. Design/methodology/approach: An open-ended, scenario-based, accounting-specific instrument was developed in collaboration with five Islamic accounting scholars to survey and measure the students’ moral competencies from an Islamic perspective. Findings: The results revealed that the students had glaring weaknesses in their moral competencies, particularly in selecting an Islamically appropriate organization to work for after graduation and the importance of diligence in completing one’s task as an accountant. The implication of these results is that these accounting programs have to critically assess the ethical content of their curricula to ensure that it is capable of developing the moral competencies of these students to an excellent level. Research limitations/implications: The implication of these results is that these accounting programs have to critically assess the ethical content of their curricula to ensure that it is capable of developing the moral competencies of these students to an excellent level. Originality/value: This paper is one of the few moral competence studies that consider the source of moral values of the respondents in measuring their moral competencies. Additionally, it provides much-needed insight into the effectiveness of a policy to address a pressing problem in the accounting profession. © 2019, Emerald Publishing Limited.